PENGEMBANGAN PENUNTUN PRAKTIKUM TIPE DISCOVERY DAN TIPE PROJECT BASED LEARNING PADA PEMBELAJARAN ELEKTROLIT DAN NON ELEKTROLIT DI SMA - Zakiah Zakiah; Albinus Silalahi; Zainuddin Muchtar (Pascasarjana Universitas Negeri Medan, 2015)
AbstractThis research is the development of practical guidance in the field of chemical education. The purpose of this research are (1) Obtain practical guide Discovery types and the type of Project Based Learning, (2) a significant difference to improving the learning outcomes that learned by using practical guidance Discovery types and the type of Project Based Learning, (3) The effectiveness of the learning process that is learned with using practical guide Discovery types and the type of Project Based Learning. The stages in this study were (1) syntax analysis Discovery learning model and Project Based Learning to know the chemistry lab guiding components in accordance with the type of Discovery and the type of Project Based Learning, (2) Prepare and develop chemistry lab guiding electrolyte and non-electrolyte material suitable with syntax type of Discovery and the type of Project Based Learning, (3) standardization or feasibility or feasibility test lab guide to the validator teachers and lecturers, (4) Implementation of practical guidance to students of class X SMA 2 Sigli, (5) to analyze the effectiveness of practical guidance Discovery types and the type of Project Based Learning in learning electrolyte and non-electrolyte that has been tested. The results of the feasibility test lab guides Discovery types 3:41 and practical guide type Project Based Learning 3:50. While the effectiveness of the use of practical guides Discovery types and the type of Project Based Learning is seen from the results of student learning in mind that the first experimental class that uses practical guide type Discovery 86.00 average with 71.4% increase in learning outcomes while using the experimental class II type Project Based practical guide Learning average of 81.75 with an increase of 58.8% learning outcomes. It can be concluded that the practical guidance Discovery types and the type of Project Based Learning feasible to be used as a guide practice in schools, with increased learning outcomes using practical guidance Discovery types of higher value than the type of practical guidance Project Based Learning.Keywords: Practical Guidance Development, Type Discovery , Type of Project Based Learning